2021
DOI: 10.1186/s12935-021-01873-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as the critical regulators of Doxorubicin resistance in breast tumor cells

Abstract: Background Chemotherapy is one of the most common treatment options for breast cancer (BC) patients. However, about half of the BC patients are chemotherapeutic resistant. Doxorubicin (DOX) is considered as one of the first line drugs in the treatment of BC patients whose function is negatively affected by multi drug resistance. Due to the severe side effects of DOX, it is very important to diagnose the DOX resistant BC patients. Therefore, assessment of molecular mechanisms involved in DOX res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 180 publications
0
17
0
Order By: Relevance
“…Despite an increasing number of molecular mechanisms underlying doxorubicin resistance in breast cancer have been reported ( Huang et al, 2018 ; Stefanski et al, 2019 ; Mirzaei et al, 2021 ; Zangouei et al, 2021 ), it remains a major obstacle to improving the clinical benefit of cancer patients. Previous studies have shown that chromatin interactions in breast cancer cells differ from normal mammary epithelial cells ( Barutcu et al, 2015 ) and estrogen-receptor binding is involved in three-dimensional (3D) genome reorganization in endocrine-resistant breast cancer ( Zhou et al, 2019 ; Achinger-Kawecka et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite an increasing number of molecular mechanisms underlying doxorubicin resistance in breast cancer have been reported ( Huang et al, 2018 ; Stefanski et al, 2019 ; Mirzaei et al, 2021 ; Zangouei et al, 2021 ), it remains a major obstacle to improving the clinical benefit of cancer patients. Previous studies have shown that chromatin interactions in breast cancer cells differ from normal mammary epithelial cells ( Barutcu et al, 2015 ) and estrogen-receptor binding is involved in three-dimensional (3D) genome reorganization in endocrine-resistant breast cancer ( Zhou et al, 2019 ; Achinger-Kawecka et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are valuable candidates for establishing the diagnosis, monitoring the progression, and predicting the possible outcomes of the disease [ 50 ]. Moreover, they can even overcome drug resistance, indicating that they have the potential to get targeted during inhibitor targeted therapy, which may increase the therapeutic efficacy [ 51 ]. In our study, we revealed 7 significant individual miRNAs, and 5 of them are supposed to play a potential diagnostic role in breast cancer detection.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BCa) accounts for almost 31% of all malignancies diagnosed in women, and ranks as the most frequent and second leading cause of cancer-related mortality in females [ 1 , 2 ]. An estimated 2,261,419 newly diagnosed BCa patients and 684,996 deaths were globally recorded in 2020 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%